Experimental measurement on friction performance of PDC bearings for oil drilling under different working conditions. (15th October 2020) - Wang, Jin; Xue, Qilong; Liu, Baolin; Li, Lixin; Li, Fangtao; Zhang, Kai; Zang, Yanbin
Highlights: Design a measurement rig to investigate the friction characteristics of the PDC bearing. Obtained the friction coefficients under different working conditions. Developed the model of friction when the viscous resistance of the fluid be considered. The influence of the rotational speed and fluid viscosity resistance on the friction coefficient is revealed. Abstract: As a kind of superhard material, the polycrystalline diamond compact (PDC) has been extensively used in engineering with its high strength and high wear resistance. Meanwhile, PDC has been increasingly used in bearing design to improve bearing capacity and service life. However, as a bearing material, its friction coefficient under different working conditions is not clear although it is a very important parameter. In this paper, the authors proposed a theoretical model of friction measurement and design a set of measurement rig to investigate the friction characteristics of the PDC bearing. The measurement equipment is developed based on the Coulomb friction model, with the three measurement environments taken into consideration: dry, water and drilling mud. A pair of thrust ball bearing was used in the measurement equipment to equilibrium axial load. But the friction coefficient of thrust ball bearing is proved far less than that of the PDC bearing in the experiment. The frictional coefficient of PDC bearings can be stabilized at about 0.12 under dry friction or water lubrication conditions and increase to 0.2 when tested under drilling fluid environment. Measuring the friction coefficient of PDC bearing -especially under drilling fluid environment can not only provide support for the design of the downhole tool where the bearing friction coefficient obviously affects the feasibility and agility of the tool but also help people to deepen the understanding of PDC materials.